Atração e comportamento de forrageio de abelhas polinizadoras em flores de cultivares de abóbora (Cucurbita moschata Duch.) em região semiárida - Lima, Marcos Venâncio (2021)
Pollination, executed by bees, is essential to ensure the reproduction of the pumpkin crop. Flowering phenology of and aspects of floral biology and nectar secretion dynamics help to understand the relationship between plants and their pollinators. In addition, volatile organic compounds (VOCs) emitted by plants may interfere with the preference of pollinators for agronomic traits within the same plant species. Thus, this study aimed to estimate the interaction of pumpkin cultivars with the environment, from the aspects of floral biology to flowering phenology, and to investigate the attractiveness and behavior of bees in flowers. Four cultivars ('Jacarezinho', 'Sergipe', 'Baiana Tropical' and Progeny CPATC) were evaluated in three productive cycles, measuring the variables: daily flower emission, stigma receptivity, anthesis period, morphometry of female and male flowers, nectar secretion pattern, soluble solids concentration and anther pollen production. The VOCs were identified in nectar and petal and interacted with the visitation of the bees. Floral visitors were identified and monitored their foraging behavior and fruit yield data were measured. The emission of male flowers was higher than the female ones, among cultivars, 'Jacarezinho' and 'Sergipe' presented the highest and lowest emission, respectively. The female flowers remain open for a longer period than the male flowers and the stigmas remained receptive until the closing of the flowers. The highest volume of nectar was with three withdrawals, and among the cultivars, 'Sergipe' showed the highest volume and 'Jacarezinho' the lowest. There was resorption of sugars in male flowers and non-resorption in females, as a strategy to ensure the visit of a pollinator. Thirty-six volatile compounds extracted from nectar and petals were identified in the rainy season, and twenty-nine compounds during the dry season. The highest number of visitors was Trigona spinipes bee, followed by Apis mellifera and Xylocopa grisescens. The correlations of the VOCs change between the sexes of the flowers towards the productive cycles in the visits of the bee species, with a positive association between the compounds methyleugenol, 1-hexanol, 2-ethyl- for visits of T. spinipes, the 1-octen-3-ol and 2-octen-1-ol with Xylocopa grisescens and 1,4-dimethoxybenzene with Apis mellifera. The differences in cultivars and cultivation conditions should be considered for the proper management of pollinators according to the attractiveness of the flowers to explore the maximum potential of the crop.